Pemanfatan Lahan Untuk Budidaya Hortikultura Melalui Pemberdayaan KWT Kecubung Batu Di Desa Blawong 1 - Ismiasih, Ismiasih; Dinarti, Siwi Istiana; Afroda, Helmi (Politeknik Negeri Cilacap, 2024)
Empty land is often found in the community environment without being used for productive activities, such as in Blawong Village 1. This community service aims to foster awareness and independence of the Women Farmers Group (KWT) in land utilization through horticultural cultivation activities. The method of community service activities is carried out by empowering KWT